Atomic bubbles in impurity-stabilized solid 4He - Lebedev, V.; Moroshkin, P.; Weis, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The optical absorption and fluorescence spectra of alkali atoms isolated in liquid and solid He matrices depend on specific macroscopic matrix properties, such as their molar volume and (anisotropic) elasticity constants, and provide thus information about the quantum matrix. We have applied optical spectroscopy to investigate the properties of a recently discovered impurity-stabilized doped 4He solid that exists in equilibrium with pressurized superfluid helium close to the solidification/melting point of pure helium. The difference between the local He density around the implanted atoms obtained in the present experiment and the average density measured earlier suggests that the impurity-stabilized solid He is in fact a porous structure filled with liquid helium.